Diário de transformações da atriz Letícia Oliver no processo de construção da personagem Inês Cecília no ciclo de leituras encenadas ovo nº 13 - FONSECA, Letícia de Oliveira (2022)
In this platform I share the Diary of Transformations of actress Letícia Olivier in the creation of the character Inês Cecília in the Cycle of Staged Readings Egg nº 13, PROEX investment in extension actions of artistic and cultural character in the year 2018. The character Inês Cecília, played by Actress-researcher and author of this TCC - Partial Requirement to Obtain a Full Degree in Theater from ETDUFPA \ ICA \ UFPA - is an assistant director with a theatrical troupe engaged in the staging of The Birds of the Jaguar Tree in Quatipuru; Specifically, the character is responsible for the production of the Staging Notebook of that montage. It is from the creation processes for this character that the transformations occur. This poetic device records the poetic ruminations performed by the cast and creators of Egg nº 13 - co-realization of the Cuíra do Pará Group. Having as its composition plan the dramaturgy itself, the writing of this blog reveals both the trajectory of the creation of Inês Cecília’s character in his fictional context as the artistic development of his interpreter in its factual context - personal relationships, groups, staging procedures, body sheet music, the creation of objects, the vocal construction and diction of the character, external and internal inspirations, local resistances and, as a theoretical-practical proposition, the concepts of Logbook and Staging Notebook. This research can be considered a continuation of a previous research, digital in nature, entitled Diary of the Performer’s Logbook: a poetic device mapping a theatrical practice also authored by the researcheractress, performed with a PIBIC \ UFPA scholarship. The two researches are part of the Group of Studies, Research and Experimentation in Theater and Universities, GEPETU, specifically integrated in the research Poetic Thinkers in the Gut of Research: Works and reflections of artists as first-rate references in the Academy of Art, by Professor Dr. Wladilene de Sousa Lima (Wlad Lima) TCC advisor.